2022
DOI: 10.12688/wellcomeopenres.17969.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of religiosity in adults from a large UK cohort using latent class analysis

Abstract: Background: Religiosity is a complex, multifaceted construct, comprising a variety of beliefs and behaviours. Much of the previous research that seeks to quantify religiosity has made use of variable-centred approaches, which place individuals on a continuum of religiosity. However, alternative approaches provide a way to examine different types of religiosity, represented by heterogeneous classes of religious (non)belief. The aim of this study was to apply a person-centred approach to understanding religious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The latent classes were labelled as: "highly religious" (characterised by believing in God/a divine power, attending a place of worship regularly and obtaining help/support from members of their own or other religious groups), "moderately religious" (believing in God/a divine power, but less likely to attend a place of worship or obtain help/support from members of their own or other religious groups), "agnostics" (not sure if believe in God/a divine power and do not attend a place of worship), and "atheists" (do not believe in God/a divine power or attend a place of worship). The latent classes derived at each time-point are broadly consistent with one another (table S1; for more details on how these latent classes were constructed, see (Halstead et al 2022)). c In the 28 years data collection, the question changed to past tense: "Did you bring your children up in your current faith/belief (including none)?"…”
Section: Datamentioning
confidence: 52%
“…The latent classes were labelled as: "highly religious" (characterised by believing in God/a divine power, attending a place of worship regularly and obtaining help/support from members of their own or other religious groups), "moderately religious" (believing in God/a divine power, but less likely to attend a place of worship or obtain help/support from members of their own or other religious groups), "agnostics" (not sure if believe in God/a divine power and do not attend a place of worship), and "atheists" (do not believe in God/a divine power or attend a place of worship). The latent classes derived at each time-point are broadly consistent with one another (table S1; for more details on how these latent classes were constructed, see (Halstead et al 2022)). c In the 28 years data collection, the question changed to past tense: "Did you bring your children up in your current faith/belief (including none)?"…”
Section: Datamentioning
confidence: 52%
“…Higher parental SEP is associated with better mental and physical health in offspring (Vukojević, 2017;Cohen et al, 2009;Lemstra et al, 2008). There is also evidence for a relationship (albeit an inconsistent one) between socioeconomic variables and religiosity (Brandt & Henry, 2012;Heaton, 2013;Horowitz & Garber, 2003;Mueller & Johnson, 1975;Schieman, 2010;Schwadel, 2015;Storm, 2017;Thompson et al, 2012), which was also identified in ALSPAC (Avon Longitudinal Study of Parents and Children) (Halstead et al, 2022;Major-Smith et al, 2022). Adverse childhood experiences are also associated with religious struggles (e.g., feelings of abandonment by God) such as the death of a loved one or life-threatening events (McCormick et al, 2017), but also a desire to connect to a higher power (Santoro et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…We used the maternal latent class membership variables derived by Halstead et al, (2022) as our indicators of religiosity in the mothers of the ALSPAC parent cohort, based upon the assumptions that they would be the primary caregiver, the classes are stable over time (D. Smith et al, 2022) and that maternal and paternal religious latent classes are associated (see Halstead et al, 2022). The latent classes are composed of a series of conditional probabilities, which are used to label and describe the classes.…”
Section: Latent Classes Of Maternal Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher parental SEP is associated with better mental and physical health in offspring (Cohen, Yoon, & Johnstone, 2009 ; Lemstra et al, 2008 ; Vukojević et al, 2017 ). There is also evidence for a relationship (albeit an inconsistent one) between socioeconomic variables and religiosity (Brandt & Henry, 2012 ; Heaton, 2013 ; Horowitz & Garber, 2003 ; Mueller & Johnson, 1975 ; Schieman, 2010 ; Schwadel, 2015 ; Storm, 2017 ; Thompson, Thomas, & Head, 2012 ), which was also identified in Avon Longitudinal Study of Parents and Children (ALSPAC) (Halstead, Heron, & Joinson, 2022 ; Major-Smith et al, 2023 ). Adverse childhood experiences (ACEs) are also associated with subsequent religious struggles (e.g.…”
Section: Introductionmentioning
confidence: 88%